TEACHING FACTORY ON IMPROVING STUDENT COMPETENCY IN BANTEN - Zaenal Ambia; Sulaeman Deni Ramdani (Universitas Sultan Ageng Tirtayasa, 2017)
SMK has an important role in the preparation of labor. SMK is required to always be able to follow the needs of the work world that continues to grow in accordance with the vision and mission objectives of SMK. This study aims to 1) to know the readiness of teaching factory implementation, 2) to identify problems of teaching factori application. This research uses quantitative descriptive. Source of data obtained from SMKN 2 Pandeglang, SMP Ypp Pandeglang, SMKN 7 Pandeglang, SMKN Agriculture Serang City, SMKN 1 Cikande, SMKN 1 Cilegon And Smkn 4 Serang City, the number of respondents amounted to 30 respondents. Data collection techniques using a questionnaire of 30 items. Technique of data analysis using quantitative descriptive statistic. Implementation of Teaching Factory Result to Student Competence Improvement, showed that 1) acquisition from aspect of readiness of human resource in aiming very good result / high with percentage 81%. Aspects of infrastructure facilities show excellent results / high percentage 79%, Aspects of cooperation readiness DU / DI percentage of 68% showed good results / high 2) Problems of teaching factory implementation can be explained. a) lack of restrictions on cooperation in schools with DU / DI b) still lack of tools and sarapa prakti from DU / DI. c) forms of cooperation undertaken not in accordance with school expectations.